Permeability evolution and water transfer in the excavation damaged zone of a ventilated gallery. (May 2016) - Pardoen, B.; Talandier, J.; Collin, F.
Abstract: The fluid transfers occurring around underground galleries are of paramount importance when envisaging the long-term sustainability of underground structures for nuclear waste disposal. These transfers are mainly conditioned by the behaviour of the surrounding material and by its interaction with the gallery air. The hydro-mechanical behaviour of the excavation damaged zone, which develops around galleries due to the drilling process, is thenceforward critical because it is composed of fractures having a significant irreversible impact on flow characteristics and transfer kinetics. Besides, the material interaction with the gallery air may engender water drainage and desaturation. Thus, a gallery air ventilation experiment, preceded by its excavation, is numerically modelled in an unsaturated argillaceous rock to study its influence on hydraulic transfers. The fractures are numerically represented with shear strain localisation bands by means of a microstructure enriched model including a regularisation method. The impact of fracturing on the transport properties is addressed by associating the intrinsic permeability increase with mechanical deformation which is amplified in the strain localisation discontinuities. Such dependence permits us to reproduce a significant permeability increase of several orders of magnitude in the excavation damaged zone, in agreement with available experimental measurements. After the excavation, the hydraulic transfers are studied through the reproduction of a gallery air ventilation experiment that implies drainage and desaturation of the surrounding rock. These transfers depend on liquid water and water vapour exchanges at gallery wall that are introduced through a non-classical boundary condition. The model prediction successfully captures the drainage and desaturation kinetics of undisturbed and damaged rock. Abstract : Highlights: Water transfers are studied around a ventilated gallery drilled in claystone. Fractures in the excavation damaged zone are represented with shear banding. Permeability modification is addressed with a strain-dependent relation. The numerical modelling successfully predicts the rock drainage and desaturation. A non-classical flow boundary condition is relevant for the air–rock interaction.